Language teacher agency in emergency online teaching. (April 2022) - Ashton, Karen
Abstract: This article examines the agency of four language teachers, and the affordances and constraints in their achievement of agency, as their routines were disrupted by the sudden shift to emergency online teaching due to the global pandemic, COVID-19. Within this larger shared critical incident, this article discusses the unique critical incidents that prompted each teacher to reflect on their practice, the agency they enacted and factors influencing the actions taken. This study provides further evidence that teachers exercise their agency in line with their professional identities, and illustrates that social structural factors feature prominently in teachers' identities and enactment of agency. The practical-evaluative dimension of agency is also further elucidated with evidence that teachers use their agency to maximise the benefits, evaluating the 'solution' adopted as an appropriate response to multiple concerns and goals. This study has important implications for teacher development highlighting the need for professional development programmes to better prepare teachers for the diversity of teaching situations which they may encounter, particularly in relation to differences in the role of the teacher, and the power dynamics and relationships between teacher, learner(s), and parents in different teaching modes.